Analyzing Factors of Environmental Pollution from Construction Sites and Proposing Solutions - Pham, Vu Hong Son; Dau, Thuy Dung (International Journal of Sustainable Construction Engineering and Technology, 2024)
Amid accelerating modernization, environmental degradation has become increasingly prevalent across various industrial sectors, with the construction industry emerging as a significant contributor. In Vietnam, construction-related pollution has reached alarming levels in both acceleration and severity. Despite regulatory measures, current mitigation efforts remain inadequate and have shown limited effectiveness in addressing pollution caused by the construction sector. This study aims to identify, analyze, and evaluate key factors contributing to environmental pollution at construction sites through a survey of industry professionals. Using SPSS software for data analysis, the research identifies five principal factors among 36 independent causes of environmental pollution. Based on these findings, the study proposes targeted interventions to reduce construction-related pollution and foster sustainable development within Vietnam’s construction sector.